När sjukt blir friskt och friskt sjukt. Pooneh Rohis Hölje och sjukdomsbegreppets innebörd - Pettersson, Cecilia (Folia Scandinavica Posnaniensia, 2024)
This article discusses how different notions of illness are portrayed in the Swedish-Iranian author Pooneh Rohi’s novel Hölje (2021). It notes the tendency to diagnose the main character, Mona, with postpartum psychosis, as discernible in the reception, but questions its suitability as a fruitful perspective for approaching the novel and the experience expressed here. Instead, a phenomenological perspective is established, focusing on how illness is perceived by the sufferer herself and what knowledge about the self, other people, and the world becomes possible to obtain in this way. Through this perspective, it becomes clear that the concepts of illness and health are given new meanings and connotations in the novel, as they are associated with the concepts of falseness and authenticity in a new and unconventional way. Thus, the novel can be read as a criticism both of biomedical science that diagnose and sort people into categories based on a medical understanding of illness, and of a broader cultural perception of what constitutes sick and healthy behaviour.